Going beyond parochialism and fragmentation in the study of international relations - Eun, Yong-Soo (Routledge, 2020)
"International Relations (IR), as a discipline, is a western dominated enterprise. This has led to calls to broaden the scope and vision of the discipline by embracing a wider range of histories, experiences, and theoretical perspectives - particularly those outside the Anglo-American core of the West. The ongoing 'broadening IR projects' - be they 'non-Western IR', 'post-Western IR', or 'Global IR' - are making contributions in this regard. However, some careful thinking is needed here in that these attempts could also lead to a national or regional 'inwardness' that works to reproduce the very parochialism that is being challenged. The main intellectual concerns of this edited volume are problematising Western parochialism in IR; giving theoretical and epistemological substance to pluralism in the field of IR based on both Western and non-Western thoughts and experiences; and working out ways to move the discipline of IR one step closer to a dialogic community. A key issue that cuts across all contributions in the volume is to go beyond both parochialism and fragmentation in international studies. In order to address the manifold and contested implications of pluralism in in the field of IR, the volume draws on the wealth of experience and research of prominent and emerging IR scholars whose contributions make up the work, with a mixture of theoretical analysis and case studies. This book will appeal to scholars and students interested in Global IR and promoting dialogue in a pluralist IR"--
Keywords: Politische Theorie; Internationale Politik; Globalisierung; International relations / Philosophy; East and West; Cultural pluralism; Aufsatzsammlung